Factorii de risc pentru plasarea tinerilor în categoria NEET: cazul Republicii Moldova - Gagauz, Olga; Crîșmaru, Mariana (Calitatea Vieții, 2024)
The proposed study investigates the phenomenon of NEET youth in the specific context of the Republic of Moldova. By focusing on identifying the risk factors that contribute to the inclusion of young individuals in the NEET category, the research aims to provide relevant information regarding the challenges that younger generations face in transition to adulthood. Utilizing statistical data and the results of the “Generations and Gender Survey”, the size and structure of NEET youth are analyzed. Applying the logistic regression method, the study distinctly explores the risk factors for NEET-unemployed and NEET-inactive. This research is committed to making valuable contributions to the scientific field, reflecting on the situation of NEET youth in a country facing multiple economic crises during the market economy consolidation period, associated with a high level of international migration, including among young people. Thus, the study completes the picture regarding the mechanisms leading to the NEET status in Eastern European countries, and provides essential information for the development and implementation of effective policies to reduce the NEET rate among young people.